Terapi Musik Dan Imajinasi Terbimbing Pada Primigravida Pre Sectio Caesarea Dengan Ansietas - Ningsih, Ratna; Jaya, Herawati; Rosyada, Tahirrou (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: In particular, women can experience psychological disorders during the perinatal stage, around 20%, one of which is anxiety. Anxiety is a normal reaction to threats that can become a psychological health problem if the anxiety continues. According to research conducted by Purwaningrum (2018) it shows that giving music therapy for 20 minutes is more effective in reducing anxiety in preoperative SC patients because it can make the mother relax and can divert the anxiety that will be faced during the surgery she will face. The purpose of giving this therapy is to find out if there is a decrease or increase in anxiety in the client. Methods: The design of this study used a descriptive method with 4 clients, namely primigravida pre sectio caesarea with anxiety nursing problems. The research data was taken using interviews and observation. The results of data collection are presented in the form of tables and narratives. Results: The implementation of music therapy nursing and guided imagery in the four primifravida pre-sectio caesarea mothers decreased anxiety levels. Conclusion: Actions that can be taken on primigravida pre sectio caesarea clients with anxiety problems can be in the form of music therapy and guided imagery and are effective to do.